Parasites of the Glory - Paolo Martore (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Conservation as a basic task of the museum rests on the recognition of artworks. However, within the domain of contemporary art, the recognition process is often demanding and controversial, demonstrating a performative and reflexive effect. As a crucial action through which Conservation defines itself by defining the artwork’s values, recognition is the moment when the neglected ideological facet of the museum’s mission comes to light.